Trilogi Kepemimpinan Islam: Analisis Teoritik terhadap Konsep Khilafah, Imamah dan Imarah - Moch. Fachrurozi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2008)
In fact, Islam have many concepts about leadership. Minimally, there are three concepts of leadership which ever aplicated in Muslim world, each of it has variaties characteristic such khilafah, imamah and imarah. Khilafah naturally is more teologis and sosiologis. As teology ,  because it has the strong relation with destination of human creating as chalifath in world, and sosiologis because in practice, election of leader process is be done by humanbeing. Imamah pure teologis as in syarat pemimpin harus ma’shum. Sementara itu imarah pure sosiologis because not based to teologis principles.